USINA DE COMPOSTAGEM: UMA OPÇÃO ECONÔMICA E SUSTENTÁVEL - Guse, Jaqueline Carla; Zulian, Aline; Ávila, Viviane Schons de; Dörr, Andréa Cristina; Rossato, Marivane Vestena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705713 The accelerated search for increased productivity and rampant use of natural resources combinedwith the emission of pollutants has motivated the concern with the environment in many sectorsof agribusiness. Through a survey of the Composting Plant Ecocitrus Cooperative, the city ofMontenegro, in the Vale do Cai, Rio Grande do Sul, aimed to analyze the basic proceduresperformed in the processing of industrial wastes in new product, the organic compound (orfertilizer), bringing a new cycle for those products that would be discarded. It was found that,besides this plant representing a place for companies discard some of their waste without harmingthe environment, it also benefits the partners that make up the producers of EcocitrusCooperative. These, in turn, receive a free compost on their properties, replacing the agrochemicalinput and having an organic citrus production.